Avulsion Fracture of the Anterior Superior Iliac Spine in a Young Athlete Detected by Point-Of-Care Ultrasound - Takaaki Mori; Takateru Ihara; Osamu Nomura (POCUS Journal, 2022)
Pelvic avulsion fractures (PAFs) are common in adolescents. X-ray is commonly used to diagnose PAF, but the use of point-of-care ultrasound (POCUS) for this purpose in pediatric emergency departments has yet to be published. We reported herein a pediatric case of anterior superior iliac spine (ASIS) avulsion fracture detected by POCUS. A 14-year-old male patient visited our emergency department for groin pain he experienced during a game of baseball. POCUS of the right ilium demonstrated a hyperechoic structure anterolaterally displaced towards the ASIS, suggesting an ASIS avulsion fracture. X-ray of the pelvis confirmed the findings and led to the diagnosis of ASIS avulsion fracture.